Towards Predicting Query Execution Time for Concurrent and Dynamic Database Workloads - Wu, Wentao; Chi, Yun; Hacigümüs, Hakan; Naughton, Jeffrey F. (Proceedings of the VLDB Endowment (VLDB 2013), 2013)
Predicting query execution time is crucial for many database management tasks including admission control, query scheduling, and progress monitoring. While a number of recent papers have explored this problem, the bulk of the existing work either considers prediction for a single query, or prediction for a static workload of concurrent queries, where by “static” we mean that the queries to be run are fixed and known. In this paper, we consider the more general problem of dynamic concurrent workloads. Unlike most previous work on query execution time prediction, our proposed framework is based on analytic modeling rather than machine learning. We first use the optimizer’s cost model to estimate the I/O and CPU requirements for each pipeline of each query in isolation, and then use a combination queueing model and buffer pool model that merges the I/O and CPU requests from concurrent queries to predict running times. We compare the proposed approach with a machine-learning based approach that is a variant of previous work. Our experiments show that our analytic-model based approach can lead to competitive and often better prediction accuracy than its machine-learning based counterpart.